A suggestion to use codeswitching as an L1 resource in the students' written work: a pedagogical strategy - Jalal, Runeela, author; Ehlers-Zavala, Fabiola, advisor; Flahive, Douglas E., advisor; Gudmestad, Robert H., 1964-, committee member (Colorado State University. Libraries, 2010)
Pakistani English has marked its presence in all genres and poses pedagogical implications for both teachers and students. Most students in English as Foreign Language (EFL) settings are unaware of how and when to use code-switching (CS) as an L1 resource in their written work to convey local social meanings as no common standard has been established for teachers and students. This situation negatively affects uniformity in instructional and assessment procedures. While the use of CS in academic settings is still a relatively new area of research, recent studies advocate the use of L1 as a resource in the classroom. This focused study provides an overview of previous CS research centered on its importance as a discourse tool in the oral and written work of multi/bilingual persons who use CS to convey social aspects which cannot be appropriately communicated through the target language (TL). Some studies observe the CS patterns found in teacher talk during instruction and advocate its use as a potential L1 resource, but they fail to address how it can be regulated in students' written work without hindering TL learning. This study fills in the gap by suggesting the use of bi-directional translation methods in conjunction with acceptability judgment tasks in order to instruct students in identifying how and when CS should be used as an L1 resource. The study is conducted with the pool of 36 students in a local university in Lahore, who read four English newspaper articles and code-switched in Urdu in pre and post-instruction stages. Paired t-test results showed significant improved results for the acceptance rates and number of attempts by the participants in the post instruction. This suggests that students can use L1 as a resource to convey concepts in the TL when properly instructed and that further research in this connection can be useful for FL learning settings.
Department Head: Bruce A. Ronda.